Rapid antimicrobial susceptibility testing using carbon screen printed electrodes in a microfluidic device - Saranya Gopalakrishnan; Diksha Mall; Subramaniam Pushpavanam; Richa Karmakar (Scientific Reports)
Abstract The development of rapid, sensitive, and affordable antimicrobial susceptibility testing (AST) is essential for controlling antibiotic overuse, thereby creating a critical checkpoint for the emerging antimicrobial resistance threat. Here, we introduce a novel method of electrochemical monitoring of bacterial growth in a diluted low-conductivity nutrient medium for rapid susceptibility testing using impedance spectroscopy. The method works on the change in charge transfer resistance exhibited by bacteria in response to antibiotics. The proposed Electrochemical Microfluidic device (ε-µD) employs low-cost carbon screen-printed electrodes and uses a simple microfluidic geometry. We explored the utilisation of a diluted nutrient medium as an electrolyte since it provides a higher charge transfer baseline signal for better sensitivity and supports the growth of the bacteria required for detection. The method enables sensitive detection of bacteria even at a low density of 84/mm2 in three hours of incubation time. For proof of concept, bacteria such as Escherichia coli and Bacillus subtilis were used, and the efficacy of the ampicillin and tetracycline drugs were tested. The experiments were done with the spiked urine samples, which correlated well with the controlled sample. The proposed system enhances the accessibility and affordability of rapid susceptibility testing, enabling its widespread use.